The Influence of Social Media on the Cultural Identity of the Millennial Generation: Indonesian Case Study - Pangesti, Maydiyan; Khaeriah, Ade Siti; Purwanto, Eko; Dwi, Aura; Nur, Azhara; Syafitri, Alexa; Shiva, Mefianda; Permata, Adinda; Intan, Nur; Azhari, Hajar (Indonesian Journal Publisher, 2024)
Results show that social media has a dominant role in shaping the cultural identity of the millennial generation. There have been significant changes in language use, with many English terms and phrases being used in everyday communication. Global fashion trends spread through social media are also widely adopted, leading to a mix of traditional and modern clothing styles. In addition, social values ​​such as freedom of expression and gender equality are more accepted and adopted by the millennial generation. Social media plays a dual role in cultural preservation and change. On the one hand, this platform enables the preservation of local culture through online communities that focus on specific cultures. On the other hand, strong foreign cultural influences can erode local cultural elements. Therefore, digital literacy and critical awareness in using social media are important to maintain a balance between adopting global culture and preserving local culture.